Managerial Production of the Morning Live Chat Broadcast Program in Maintaining the Existence of Rri Pro 2 Jakarta - Suparyadi Suparyadi; Istiqomah Istiqomah (Peneliti.net, 2023)
A broadcast program cannot run according to the listener's wishes because there are several regulations that burden a producer and the production team in channeling their creative ideas, where a producer and production team must be able to pay attention to the wants and needs of listeners and apply them to a broadcast program to maintain existence. The purpose of this study was to determine the managerial production of the Morning Live Chat broadcast program in maintaining its existence at RRI Pro 2 Jakarta. The research method used in this study is a qualitative descriptive method, by conducting observations and direct field interviews with informants. For data processing techniques, used data reduction techniques, data presentation and draw conclusions. As for the validity of the data using source triangulation techniques. The results of this study indicate that the managerial process of RRI refers to efficiency and effectiveness, where all production processes must be determined, regulated, direct and evaluated in the setting agenda. In addition, organizational communication in the agenda setting carried out by the production team has the aim of getting changes to follow existing developments and follow issues that are currently popular. Although RRI has a formal hierarchy of organizational authority, this does not mean that RRI does nothing to maintain its existence by making changes that follow the wishes and needs of listeners. In the end, the managerial production of the MORNING LIVE CHAT broadcast program in maintaining the existence of RRI PRO 2 Jakarta, is still referring to the